The Toll-like receptor 4 antagonist TAK-242 protects against chronic pancreatitis in rats - Pan, Long-Fei (Mol Med Rep, 2017)
Chronic pancreatitis is a progressive disease characterized by irreversible morphological changes to the pancreas, typically causing pain and permanent loss of function. It is a poorly understood disease with the pathogenesis remaining unclear. The authors' previous data demonstrated that the inhibition of Toll-like receptor 4 (TLR4) using TLR4 antagonist kinase (TAK)-242 attenuates taurocholate-induced oxidative stress via the regulation of mitochondrial function in the pancreatic acinar cells of mice. In the present study, the effect of TAK-242 on trinitrobenzene sulfonic acid (TNBS)-induced chronic pancreatitis was investigated in rats. The results revealed that TAK-242 attenuated the severity of chronic pancreatic injury, and regulated extracellular matrix secretion and cellular immunity. In addition, TAK-242 treatment significantly decreased cell apoptosis, as evidenced by the reduction in Terminal deoxynucleotidyl transferase dUTP nick end labeling-positive cells in pancreas tissue sections, and also promoted cell proliferation in TNBS-treated animals. Furthermore, the results of the calibrated von Frey filament assay demonstrated that TAK-242 could prevent the pancreatitis-induced referred abdominal hypersensitivity. In summary, TAK-242 exhibits protective effects against TNBS-induced chronic pancreatitis and may be a potential therapeutic strategy for the treatment of patients with chronic pancreatitis.